(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article provides information about the historical development of trade, science, and urbanization in the territory of Tashkent city. It also highlights the current share of Tashkent in foreign trade turnover, along with insights into bordering countries and other developed nations with a high share in Tashkent’s foreign trade relations.